2019
DOI: 10.1007/s00417-018-04227-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the posterior corneal elevation and biomechanics after SMILE and LASEK for myopia: a short- and long-term observation

Abstract: Purpose This study compares the posterior corneal elevation and corneal biomechanics after small incision lenticule extraction (SMILE) and laser-assisted subepithelial keratomileusis (LASEK) for myopia correction in a short-and long-term observation. Methods This prospective study included 32 patients in the SMILE group and 32 patients in the LASEK group. Corneal posterior central elevation (PCE), posterior mean elevation (PME), corneal back power (Kb), and anterior chamber depth (ACD) were evaluated with Pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
4
25
2
Order By: Relevance
“…Seventeen studies reported a cap thickness between 100 to 120 μ m [25, 30, 3941, 45, 4753, 55, 56, 58, 59]. Only one study reported a 90 μ m thickness cap [36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies reported a cap thickness between 100 to 120 μ m [25, 30, 3941, 45, 4753, 55, 56, 58, 59]. Only one study reported a 90 μ m thickness cap [36].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study reported a 90 μ m thickness cap [36]. The cap diameter was between 7.2 to 8 mm in 16 studies, [25, 30, 36, 38, 41, 4551, 53, 5860] and the diameter of the optical zone was between 6 to 7 mm in 19 studies [25, 30, 36, 3841, 45, 4749, 5156, 58, 59]. Twelve studies were performed with an energy between 115 to 190 nJ [30, 36, 38, 40, 41, 45, 47, 4951, 53, 54, 58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from previous studies suggested that anterior segment changes would last for a long time, while posterior segment changes are only observed for a short time and then gets resolved. Prior studies have reported that PCE and ACD decreased after surgery and even several years later [ 6 , 7 ], and this change was more significant in younger patients [ 12 ]. It has also been reported that changes in elevation correlated with residual bed thickness [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cornea biomechanics decrease after both LASIK and SMILE [4,5]. Posterior corneal elevation (PCE) and anterior chamber depth (ACD) are also reduced [6,7], but few studies have investigated changes in the retina.…”
Section: Introductionmentioning
confidence: 99%